A felszolgálási díj szabályozásáról az alapvető jogok biztosának eljárása kapcsán - Hámori, Antal (Debreceni Jogi Műhely, 2017)
The article introduces the statutory regulation of service charges in relation to the procedure of the Commissioner for Fundamental Rights in a complex manner, by referring to all affected parts of the statutory system providing a detailed and critical analysis, reasoning, furthermore the article also refers to the statutory dogmatic, constitutional issues, controversies, maladministration and interpreting questions related to service charges, by also making reference to the halts in consumer protection – repealing the 15% upper limit. The article presents the answer of the Commissioner for Fundamental Rights and the necessary reflection to this answer. The author publishes his thorough and firm opinion, which takes into consideration consumer protection and discrimination aspects, in a usable manner for legislators and law enforcement bodies, and summarises the final conclusions, „missing items” complied in nine points.